2018
DOI: 10.1007/s11096-018-0698-5
|View full text |Cite
|
Sign up to set email alerts
|

Trends in reporting drug-associated liver injuries in Taiwan: a focus on amiodarone

Abstract: Background A pharmacovigilance database of real-world adverse drug reaction (ADR) reports is helpful for characterising adverse events and identifying new signals after drug approval. Objective This study aimed to analyse trends of ADR reporting in relation to liver injury and to delineate critical factors for suspected drug-related hepatotoxicity with a focus on reports associated with amiodarone. Setting The 2000-2014 Taiwan pharmacovigilance database. Method Relevant Standardized Medical Dictionary for Regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Nonetheless, solid evidence for elusive intangible drug covariates associated with either therapeutic or toxic effects are often not readily available upon regulatory approval. It is valuable to perform studies with RWD from real settings, as demonstrated in Table 1 , to supplement awaited determinants of drug effects for clinical decision making. By health record (electronic and paper) review, nephrotoxic polypharmacy exhibited a significant association with contrast medium–induced nephropathy among inpatients undergoing contrast‐enhanced computed tomography.…”
Section: Sources and Features Of Rwd To Identify Complex Drug Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nonetheless, solid evidence for elusive intangible drug covariates associated with either therapeutic or toxic effects are often not readily available upon regulatory approval. It is valuable to perform studies with RWD from real settings, as demonstrated in Table 1 , to supplement awaited determinants of drug effects for clinical decision making. By health record (electronic and paper) review, nephrotoxic polypharmacy exhibited a significant association with contrast medium–induced nephropathy among inpatients undergoing contrast‐enhanced computed tomography.…”
Section: Sources and Features Of Rwd To Identify Complex Drug Factorsmentioning
confidence: 99%
“…By health record (electronic and paper) review, nephrotoxic polypharmacy exhibited a significant association with contrast medium–induced nephropathy among inpatients undergoing contrast‐enhanced computed tomography. Through investigations of health records and postmarketing surveillance data, drug dispositions (interacting drugs, amiodarone cumulative dose, and adjusted average daily dose) and host factors (shorter height and smaller body surface area) were reported to be important predictors of amiodarone‐related liver injury. Studies of health claims helped identify the inverse associations between dose intensity (bisphosphonates or statins) and the likelihood of unintended risk (esophageal cancer or poststroke epilepsy).…”
Section: Sources and Features Of Rwd To Identify Complex Drug Factorsmentioning
confidence: 99%
See 3 more Smart Citations